Use of anatomical, chemical, and molecular genetic characteristics in the quality control of medicinal species: a case study of sarsaparilla (Smilax spp.) - Martins, Aline R. [UNESP]; Soares, Marli K. M.; Redher, Vera L. G.; Bajay, Miklos M.; Villela, Priscilla M. S.; Zucchi, Maria I.; Appezzato-Da-Gloria, Beatriz (Springer, 2014)
Species of the genus Smilax, popularly known as sarsaparilla, are used in folk medicine as a tonic, an anti-rheumatic, and an anti-syphilis treatment, and are sold in Brazilian drugstores without any quality control regarding their origin and efficacy. The origin of the material is mainly based on wild extraction. Quality control of herbal drugs should include a more reliable identification of the source involving characterization and definition of their anatomical and chemical characteristics. The current study aimed to verify whether the combined use of anatomical, chemical, and molecular genetic characteristics might be useful in the quality control of medicinal plants, specifically the sarsaparilla sold in compounding drugstores in the state of So Paulo, Brazil. Root samples were subjected to conventional light microscopy and scanning electron microscopy. To determine the chemical profile, thin-layer chromatography (TLC) was applied to ethanol extracts of the roots. The chemical profile of the chemical material sold in stores was compared with the previously determined profiles of medicinal Smilax species (S. goyazana, S. rufescens, S. brasiliensis, S. campestris, S. cissoides, S. fluminensis, S. oblongifolia, and S. polyantha). Although there was considerable similarity between the anatomical structure of the commercial sarsaparilla and the structure reported in the literature for the Smilax species, there were differences in the phloem organization and in the presence of a series of idioblasts containing raphides, phenolic idioblasts, and metaxylem in the center of the plant structure. TLC analysis of the commercial ethanol extracts revealed spots with colors ranging from yellow to green. In addition, the same spots showed components with the same retention factor (Rf), indicating chemical similarity between the different samples. However, the distribution pattern of the spots, as well as the Rf of the commercial samples, differed from those obtained for the eight species of Smilax, which were very similar to each other. Comparing the groups examined in the present study with regard to microsatellite markers and DNA barcoding revealed that commercial sarsaparilla is genetically different from the eight species of Smilax known for their medicinal properties in Brazilian ethnobotanical surveys. This seriously calls into question their effectiveness. This case study of sarsaparilla demonstrates the utility of anatomical, chemical, and molecular genetic characteristics in the quality control of medicinal plants.
Keywords: Thin-layer chromatography; Histology; Ethnobotany; MicrosatellIte markers; DNA barcoding; Smilax